Challenges to regulate products containing bisphenol A: Implications for policy - Nicolas D. Mandel; Brenda Gamboa-Loira; Mariano E. Cebrián; Ángel Mérida-Ortega; Lizbeth López-Carrillo (Instituto Nacional de Salud Pública, 2019)
Bisphenol A (BPA), found in plastics and epoxy resins, is one of the most studied chemicals. BPA is regarded as an endocrine disruptor and has been related to adverse health effects in humans. However, some regulatory agencies around the world have concluded that BPA is safe at current human exposure levels. As the scientific community attempts to settle the debate on BPA's health effects, regulatory agencies have been put into a challenging public health policy situation. The United States has implemented no regulatory actions due to safety concerns, while Europe has used the precautionary principle to guide its regulation in the face of scientific uncertainty. In this paper, we explore the debate surrounding BPA regulation and the possibility for countries to introduce guidelines, using Mexico as an example. Policy change determinants analysis suggest that countries can and should impose regulations on BPA.